2019
DOI: 10.1021/acsami.9b16599
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical In2O3@SnO2 Core–Shell Nanofiber for High Efficiency Formaldehyde Detection

Abstract: In this work, three-dimensional (3D) hierarchical In2O3@SnO2 core–shell nanofiber (In2O3@SnO2) was designed and successfully prepared via a facile electrospinning and further hydrothermal methods. Vertically aligned SnO2 nanosheets uniformly grown on the outside surface of In2O3 nanofibers were clearly observed by field emission scanning electron microscopy. Besides, hierarchical core–shell nanostructure of In2O3@SnO2 was characterized by elemental maps using scanning transmission electron microscopy. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(74 citation statements)
references
References 69 publications
3
71
0
Order By: Relevance
“…It can be concluded that a low detection limit of < 5 ppm can be achieved for our network based sensors. However, the measured response and recovery time of network sensor are in the order of minutes, much longer than the nanomaterial-based sensors [53,54]. Compared with the test system and sensing materials in the reported sensors, we believe that the long response and recovery time in our work can be attributed to the following two reasons.…”
Section: Gas-sensing Performancementioning
confidence: 83%
“…It can be concluded that a low detection limit of < 5 ppm can be achieved for our network based sensors. However, the measured response and recovery time of network sensor are in the order of minutes, much longer than the nanomaterial-based sensors [53,54]. Compared with the test system and sensing materials in the reported sensors, we believe that the long response and recovery time in our work can be attributed to the following two reasons.…”
Section: Gas-sensing Performancementioning
confidence: 83%
“…The crystal structure of the samples could be detected from XRD results [20], as shown in Fig. 1a Figure 1b shows that ZnTiO 3 sample is micron-scale irregular blocks structure.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reports a 3D hierarchical In 2 O 3 @SnO 2 coreshell nanofiber (In 2 O 3 @SnO 2 ) designed using vertically aligned SnO 2 nanosheets uniformly grown on the outside surface of In 2 O 3 nanofibers and tested for the sensing performance of formaldehyde (HCHO) [121]. The sensing performance of the In 2 O 3 @SnO 2 nanocomposite was found to possess the highest response value, fast response/recovery speed, best selectivity, and lowest HCHO detection limit which were attributed to the synergistic effect of large specific surface areas of SnO 2 nanosheet arrays, abundant adsorbed oxygen species on the surface, unique electron transformation between core-shell heterogeneous materials, and long electronic transmission channel of SnO 2 transition layer [121].…”
Section: Metal Oxide Nanostructures In Sensorsmentioning
confidence: 99%